The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1074/jbc.m702354200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repression by a Conserved Intronic Sequence in the Nicotinic Receptor α3 Subunit Gene

Abstract: The genes encoding the nicotinic acetylcholine receptor ␣3, ␣5, and ␤4 subunits are genomically clustered. These genes are co-expressed in a variety of cells in the peripheral and central nervous systems. Their gene products assemble in a number of stoichiometries to generate several nicotinic receptor subtypes that have distinct pharmacological and physiological properties. Signaling through these receptors is critical for a variety of fundamental biological processes. Despite their importance, the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 98 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…Several studies, looking at the transcriptional level, have revealed a cell-type specific enhancer positioned in the rat β4 3′-UTR [37], [39], [42], [44], [48], [50]. By contrast, we found decreased luciferase expression in all our test plasmids when compared to the empty pGL3 vector, along with no differences among cell lines tested.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Several studies, looking at the transcriptional level, have revealed a cell-type specific enhancer positioned in the rat β4 3′-UTR [37], [39], [42], [44], [48], [50]. By contrast, we found decreased luciferase expression in all our test plasmids when compared to the empty pGL3 vector, along with no differences among cell lines tested.…”
Section: Discussionsupporting
confidence: 40%
“…Although the transcriptional regulation of the CHRNA5/A3/B4 cluster of genes has been extensively studied in rats by several groups [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], little is known about the impact of human non-coding SNPs in this cluster of genes on the expression of these subunits. Only few studies describing the functional features of the α3 nAChR [51], [52], [53], [54] and α5 nAChR [55] subunit promoters have been done using human sequences, but none of them have looked at rs1948, located in the 3′-untranslated region (3′-UTR) of CHRNB4 .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the virus was resuspended in 50-100 µl 1x PBS, aliquoted and stored at -70 °C. The titer of concentrated lentivirus was determined by transducing 1  10 Yellow boxes: exons, green box: eGFP cassette, white box: polyadenylation signal (pA), black arrows: direction of transcription, red crosses: truncated transcription, cis-regulatory elements marked in red: conserved non-coding region (CNR4), 43' enhancer (Xu et al, 2006), E1/E2: SP1 and SP3 binding sites (Bigger et al, 1997) and 3-i: transcriptional silencer (Medel and Gardner, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The upstream sequences of Chrna5, encoding exon 1 splice variants (Flora et al, 2000), are missing in the BAC transgene ( Figure 3A). To promote correct expression of Chrnb4, the BAC included the intergenic and 5' flanking regions encompassing the cis-regulatory elements that coordinate co-transcriptional control of the genes in the cluster (Bigger et al, 1997;Medel and Gardner, 2007;Xu et al, 2006). As a result of these modifications in the BAC transgene, these mice (referred to as Tabac mice for Transgenic a3b4a5 cluster) express high levels of 4 but not 5 ( Figure 3B), and expression of 3 is replaced by expression of an eGFP reporter cassette to monitor the sites expressing the transgene ( Figures 3C-H).…”
Section: Transgenic Mice Of the Chrnb4/a3/a5 Gene Cluster (Tabac Mice)mentioning
confidence: 99%